Single-Phase PFC Converter for Plug-in Hybrid Electric Vehicle Battery Chargers - Shakil Ahamed Khan; Md. Ismail Hossain; Mousumi Aktar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
In this paper, a front end ac–dc power factor correction topology is proposed for plug-in hybrid electric vehicle (PHEV) battery charging. The topology can achieve improved power quality, in terms of power factor correction, reduced total harmonic distortion at input ac mains, and precisely regulated dc output. Within this context, this paper introduces a boost converter topology for implementing digital power factor correction based on low cost digital signal controller that operates the converter in continuous conduction mode, thereby significantly reducing input current harmonics. The theoretical analysis of the proposed converter is then developed, while an experimental digital control system is used to implement the new control strategy. A detailed converter operation, analysis and control strategy are presented along with simulation and experimental results for universal ac input voltage (100–240V) to 380V dc output at up to 3.0 kW load and a power factor greater than 0.98. Experimental results show the advantages and flexibilities of the new control method for plug-in hybrid electric vehicle (PHEV) battery charging application.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.1255